How to overcome endosomal entrapment of cell‐penetrating peptides to release the therapeutic potential of peptides?. Issue 6 (7th May 2020) - Nadal‐Bufí, Ferran; Henriques, Sónia Troeira
Abstract: Peptides gained a renascent interest as alternative pharmaceuticals, and in particular as anticancer drugs to inhibit intracellular proteins involved in cancer pathways, inaccessible to other pharmaceutical agents. However, the use of peptides as therapeutics is still limited by difficulties in reaching the protein target located in the cytosol. Cell penetrating peptides (CPPs) are being explored as tools to deliver therapeutic peptides inside cells, but they often enter cells using endocytic pathways and become entrapped inside endosomes. Therefore, a strategy to unleash the potential of peptides as therapeutics is to control the release of CPPs from endosomes. In this review we summarize recent strategies employed to improve endosomal escape of CPPs. Lessons learned from these studies can guide the design of CPPs as tools to deliver peptide sequences able to inhibit cancer targets and accelerate their development as therapeutics. Abstract :